Quick Response Code Indonesian Standard as a Digital Payment Solution to Increase the Turnover and Reduce the Circulation of Counterfeit Money - Ayuningtyas, Amalia; Adinugraha, Hendri Hermawan; Sulthoni, Muhammad (Institute Of Advanced Knowledge and Science, 2024)
With the increasing use of the internet and smartphones in Indonesia, the use of digital payment technology is increasing. The advantage of cashless payment is that it is very convenient for users because it allows payments to be made easily and quickly without using cash. Especially during the outbreak of the Covid outbreak, there was a critical decline in the turnover of Micro, Small and Medium Enterprises (MSMEs). In this case, MSME players must keep up with the times of digitalization, especially by utilizing the Quick Response Code Indonesian Standard (QRIS) system that has been provided by the Indonesian government. On the other hand, the rampant circulation of counterfeit banknotes has made some parties, especially micro, small and medium enterprises, feel uncomfortable receiving counterfeit Rupiah. This research aims to find out QRIS as a digital payment solution that can increase the turnover of Micro, Small and Medium Enterprises (MSMEs) while also reducing the circulation of counterfeit money in Indonesia. This research uses a qualitative descriptive method with a systematic literature review. The data analysis technique used qualitative analysis that describes factual information. This study shows that QRIS can increase the sales turnover of MSMEs because QRIS is a digital payment solution that can make it easier for MSMEs to run their businesses in an effort to improve service quality and competitiveness, and is expected to increase interest in repeat visits and increase profits. The use of QRIS as a payment medium makes the transaction process with consumers easier, faster and safer. In addition, it can prevent the spread of counterfeit banknotes or counterfeit rupiahs and reduce the risk of counterfeit currency fraud or counterfeit rupiahs.